The Construction and Analysis of Infiltrating Immune Cell and ceRNA Networks in Diabetic Foot Ulcer - Zeng, Lin; Zhang, Pengxiang; Fang, Zebin; Liu, Deliang; Li, Huilin; Qu, Xin; Chu, Shufang; Zhao, Hengxia; Liu, Xuemei; Lee, Maosheng (Frontiers in Endocrinology, 2022)
Diabetic foot ulcer (DFU) is a severe complication characterized by low-grade inflammation, which could be associated with specific competitive endogenous RNAs (ceRNAs) and infiltrating immune cells. Nonetheless, there are no reliable biomarkers for detecting inflammation in DFU. Therefore, it is essential to explore potential biomarkers for the accurate diagnosis and treatment of DFU. Hence, we constructed a ceRNA network, having 20 differential expression circRNA (DEcircRNAs), 11 differential expression microRNAs (DEmiRNAs), and nine differential expression mRNAs (DEmRNAs). Functional enrichment analysis demonstrated that DFU was mainly enriched in VEGF and T cell receptor signaling. In addition, CIBERSORT estimation indicated that CD8+ T cells and Monocytes were significantly related to the expression of IL-6, a DFU-specific inflammation factor. Finally, we identified some significant ceRNAs (JUNB, GATA3, and hsa-circ-0049271, has-circ-0074559) and infiltrating immune cells (CD8+ T cells and Monocytes) that might be related to DFU inflammation.